(3GdaJGhi GdJGJGQNGfjIs - (3YGde Hf YdGA GdMfaj,J (B286 (3g` s
(3ChdgG (B:s
(3cJGH GdMOhO GdcGai GdMO ai GdTQY GSe GdYbhHI ebOQI , jLH MbkG ddg JYGdi , adGjSei GdJYRjR hdG GdbUGU dCfg Mb ddYHO s
(3BNQgG (B:s
(3dGJHWd TgGOI TghOgG , hjKHJ HPdc HWdGf OYhGgG djSJ HTQW dKHhJ GdMQeI hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdejcQhajde Ydi YdHJjfs
(3cJHJ eOGNd GdaUhd hGdcJH GdJi jfbd YfgG HGdMeQI s
(3Hg eWGdH ddcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs